Principles of engineering economic analysis - White, John A.
This concise book provides engineers with the tools to evaluate the cost of their work and convey the project to key decision makers. It follows an integrative approach that arms them with a seven-step Systematic Evaluation and Analysis Technique as well as a strong understanding of cash flows. The new fifth edition has also been expanded from eight to 16 chapters, covering critical topics such as time value of money, measures of worth, depreciation, inflation, and capital rationing. Practicing engineers will be able to apply these principles and techniques to make the most effective economic decisions.